USING DICTOGLOSS TECHNIQUE TO IMPROVE STUDENTS’ WRITING SKILL - Huda, Moh. Choirul; Rahadianto, Piping (Universitas Muhammadiyah Palembang, 2019)
This study is aimed at upgrading the students’ writing skill by employing Dictogloss technique as the teaching technique in writing class. The setting and participants were the eleventh grade students totally 20 students at MA Sunan Giri Gondang. The design of this research is a classroom action research consisting 4 steps, such as planning, acting, observing, and reflecting. The data collection methods were writing test, interview to teacher and student, observation, field notes, and questionnaire. The findings show that the students’ writing skill got improvement after being taught using Dictogloss technique. The score mean increased from 66,9 (preliminary study) to 74,3 (Cycle 1) to 77,6 (Cycle 2). It can be concluded that the implementation of Dictogloss technique can improve the students’ writing skill.